Performance assessment of swarm robots - (:unkn) unknown (My University, 2009)
Swarm intelligence is the emergent collective intelligence of groups of simple autonomous agents which are autonomous subsystems that interact with their environment. This paper presents a performance evaluation system for swarm robots. The model proposed includes a set of performance assessment criteria and performance assessment and monitoring system. The proposed approach is developed for swarm robots developed for health system responsible for delivery, guidance, monitoring, recognition, and delivery which a project in European 6 th Framework Research Program and carried out by several European nations. © 2009 Springer Berlin Heidelberg.
Keywords: Performance assessment; Swarm robots